Discurso político-partidário: o antagonismo entre a Federação e o Correio do Sul (1922) - Ribeiro, Paula Vanessa Paz (2014)
This work is linked to the historiographical perspective of intellectual history. Based on that, it aims to analyze and to compare the content and form of the rhetoric of the partisan political discourse of the newspapers A Federação and Correio do Sul in the electoral process of Rio Grande do Sul in 1922. The analysis and the interpretation of partisan political discourse of the newspapers was carried out through the theoretical and methodological contributions of Pocock (2003), in the study of political discourse performance and the relationship between context and action; the operation modes of meaning and action of ideological symbolic strategies written by John Thompson (2009) and, particularly, the theory of argumentation of Perelman and Tyteca, with regard to the linking modes of argumentation. From the reading and interpretation of the rhetorical and ideological strategies applied in partisan political discourse of newspapers, it became possible to assume the way journalists perceived the events and how they interacted with the audience and readers. In the political context of 1922, the content and form of political discourse were defined according to the discursive situations that arose from events and confrontation with the political opponent. On one side was A Federação, representing the Partido Republicano Rio-Grandense; and on the other side, the Correio do Sul, representing the Partido Federalista and Aliança Libertadora. Once they were in opposing political boundaries, they developed a combative and competitive discourse in order to face the opponent and convince readers to join their political cause.